Impact of post-remission therapy in patients aged 65–70 years with de novo acute myeloid leukemia: a comparison of two concomitant randomized ALFA trials with overlapping age inclusion criteria - Itzykson, Raphael (Ferrata Storti Foundation, 2011)
BACKGROUND: There is no standard post-remission therapy in older patients with acute myeloid leukemia. DESIGN AND METHODS: From 1999 to 2006, the Acute Leukemia French Association group ran two concurrent randomized trials with overlapping inclusion criteria for patients aged 65 to 70 with acute myeloid leukemia, with different post-remission strategies: two intensive courses in the 9801 trial, one intensive course or six outpatient courses in the 9803 trial. We analyzed the outcome of these patients per protocol and per post-remission therapy. RESULTS: Two hundred and eleven patients aged 65 to 70 years with de novo acute myeloid leukemia were enrolled in trial 9801 (n=76) or 9803 (n=135). The patients in the two trials had comparable white blood cell counts (P=0.3), cytogenetics (P=0.49), and complete remission rates (70% and 57%, respectively; P=0.17). Overall survival was identical in both trials (32% and 34% at 2 years, respectively; P=0.71). Overall survival after complete remission was identical in the 103 of 130 patients who received the planned post-remission courses (n=44 with two intensive courses, n=28 with one intensive course, n=31 with six outpatient courses; 41%, 55%, and 58% at 2 years, respectively; P=0.34). Even in patients with favorable or normal karyotype (n=97), overall survival from complete remission was not improved by more intensive post-remission therapy. CONCLUSIONS: In patients aged 65 to 70 years with de novo acute myeloid leukemia in complete remission after standard intensive induction chemotherapy, there is no apparent benefit from intensive post-remission therapy. (ClinicalTrials.gov Identifiers: NCT00931138 and NCT00363025)